Note on the first Occurrence of Trilocha (=Ocinara) Varians Walker (Bombycidae : Lepidoptera) as a Pest of Pipal Tree (Ficus religiosa L.) in Madurai, Tamil Nadu - Rajavel, D. S.; Shanthi, M. (Indian Forester, 2007)
No abstract